PO003 Iliopsoas haematoma presenting as painless weakness. (1st December 2017) - AlMasri, Omar; Kankara, Chenchi Reddy; Weatherby, Stuart
Abstract : Spontaneous iliopsoas haematoma is an uncommon complication of anticoagulation. Such bleeding can be life threatening and therefore early recognition is important. In the published literature the universal presenting symptom is pain. We report on the unusual case of an elderly patient who was anticoagulated with Warfarin for Atrial fibrillation, and who presented with painless weakness of the right lower limb. Anticoagulation was reversed and her condition was managed conservatively. Her case is presented in the context of the published literature.